IMPROVING PHYSICAL TRAINING INDICATORS OF STUDENTS IN HIGHER EDUCATION INSTITUTIONS USING KURASH ELEMENTS - Jumaqulov J. M. (Bright Mind Publishing, 2025)
This article uses the methods necessary to improve the physical fitness indicators of higher education students using kurash elements. On how important physical training is in the lives of students.
Keywords: Wrestling, sports, elements, speed, individual actions, technical and tactical exercises, factor, lifestyle, exercises, physical training, sports networks, pedagogical approach, repetition method, basic endurance, dynamic and static directions.